Epithelioid Hemangioma of Lingual Alveolar Mucosa: An Immunohistochemical Case Report. (12th February 2014) - Nangia, Rajat; Puri, Abhiney; Gupta, Rakhi; Bansal, Sucheta; Negi, Amita; Chauhan, Isha
Abstract : Epithelioid hemangioma is a rare benign vascular lesion that presents as a nodular lesion in the skin of head and neck region. It is a superficial vascular entity which can either be due to tumor or reactive lesion, but the exact etiology is still unknown. We hereby present a rare case which has been reported with the history of small nodular-like growth on mandibular buccal and lingual area. The excisional biopsy was performed and tissue was submitted for histopathological diagnosis. The immunohistochemistry was performed to check the expression of CD31 marker which proved that origin of epithelioid cells was vascular.